Optimizing Digital Marketing Strategies in Increasing Consumer Buying Interest in Target Face Cushion Products: An Empirical Study on Vision Archery Cirebon - Mayang Fuji Asih; Heru Cahyono; Dewi Pranata Motik (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2026)
This study aims to determine and analyze the influence of digital marketing strategies on online consumer buying interest at Vision Archery Cirebon Store. This research is a type of quantitative research using questionnaire and documentation approaches. Data collection techniques in this study use questionnaires or questionnaires that are distributed to obtain data on the influence of digital marketing strategies (X) and documentation to obtain data on online consumer buying interest (Y). This study is a sampling study because it took part of the number of consumers at the Vision Archery Cirebon Store in the last six months which amounted to 1,260 people with 94 respondents using the calculation of the slovin formula. The results of this study show that the variable influence of digital marketing strategy has a positive and significant effect on consumer buying interest in target face bearing products at Vision Archery Cirebon Store. This is based on the results of the F test with a calculated F value of 115.599 and a sig value of 0.000 which < 0.05 and based on the results of the t test with a sig value of < 0.05 and based on the results of a simple linear regression analysis which has a unidirectional or positive regression coefficient value which means that the better the digital marketing strategy is used, it will increase the amount of consumer buying interest.